Diagnostic Accuracy of D-Dimers for Predicting Pulmonary Embolism in COVID-19-Patients. (December 2021) - Laouan Brem, Falmata; Asmae, Boudouh; Amane, Yassine; Bouazzaoui, Mohammed-Amine; Chaymae, Miri; Rasras, Hammam; Nasri, Siham; Abda, Naima; Skiker, Imane; Kouismi, Hatim; Zakaria, Bazid; Ismaili, Nabila; et al.
Importance: Proinflammatory and hypercoagulable states with marked elevation seen in D-Dimer levels have been accurately described in patients infected by the SARS- Cov2 even without pulmonary embolism (PE). Objectives: To compare D-dimers values in patients infected by the novel Coronavirus 2019 (COVID-19) with and without PE and to establish an optimal D-dimer cut-off to predict the occurrence of PE, which guides pulmonary computed tomography angiography (CTPA) indication. Methods: We retrospectively enrolled all COVID-19-patients admitted between October first and November 22th, 2020, at the University Hospital Center of Mohammed VI, Oujda (Morocco), suspected to have PE and underwent a CTPA. Demographic characteristics and blood test results were compared between PE-positive and PE-negative. The receiver operating characteristics (ROC) curve was constructed to establish an optimal D-Dimer cut-off to predict the occurrence of PE. Results: The study population consisted of 84 confirmed COVID-19-patients. The mean age was 64.93 years (SD 14.19). PE was diagnosed on CTPA in 31 (36.9%) patients. Clinical symptoms and in-hospital outcomes were similar in both groups except that more men had PE ( p = .025). The median value of D-dimers in the group of patients with PE was significantly higher (14 680[IQR 33620-3450]ng/mL compared to the group of patients without PE 2980[IQR 6870-1600]ng/mL [P < .001]. A D-dimer at 2600 ng/mL was the optimal cut-off for predicting PE with a sensitivity of 90.3%, and AUC was .773[CI 95%, .667 −.876). Conclusion: A D-dimer cut-off value of 2600 ng/mL is a significant predictor of PE in COVID-19-patients with a sensitivity of 90.3%.